Intention to seek information on cancer genetics - J.E. Andrews; J.D. Johnson; D.O. Case; S. Allard; K. Kelly (Information Research: An International Electronic Journal)
Objective. The public has a high interest in seeking personal genetic information, which holds implications for health information seeking research and health care policy. Rapid advances in cancer genetics research promise early detection, prevention and treatment, yet consumers may have greater difficulty finding and using the information they may need to make informed decisions regarding their personal health and the future of their families. Design. A statewide telephone survey was conducted of non-institutionalized Kentucky residents 18 years of age or older to investigate factors associated with the intention to seek cancer genetics information, including the need for such information seeking help. Results. The results show that intention to seek cancer genetics information, if testing were readily available, is moderately high (62.5% of those responding; n=835), and that status as a racial minority, the perception that cancer runs in one's family, and frequent worrying about cancer risk are statistically significant predictors of intent to seek genetics information. Conclusion. . We argue that an already complex health information environment will be even more difficult for individuals to navigate as genetic research becomes more ubiquitous in health care. An increase in demand for genetics information in various forms, as suggested by these results and those of other studies, implies that enduring intervention strategies are needed to help individuals acquire necessary health information literacy skills, with special attention given to racial minorities.